Application of Large Area TiO2 Photoelectrode on Dye-Sensitized Solar Cells - Natalia M. Nursam; Lia Muliani; Jojo Hidayat (National Research and Innovation Agency, 2013)
The scale-up of dye-sensitized solar cell (DSSC) has been a big issue as the DSSC technology process progresses from laboratory scale to large area applications. Meanwhile, this type of solar cell has been of great interest among PV scientist and academics as it can be produced in lower-cost processes compared to the conventional solar cells which are mostly fabricated from silicon. The fabrication of DSSC prototypes with a relatively large active area of 9x9 cm2 are demonstrated in this paper. Large area of TiO2 surface has been shown to significantly increase the ISC, as well as VOC and Pmax. Nevertheless, deterioration of fill factor (FF) was observed as the result of the increase on series resistance with respect to the increase in the photoelectrode area.